Exploring the Effects of Video Gaming on Memory and Mood in Youth - Alishba Tariq; Shagufta Javaid; Fatima Irshad, (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
This study investigates the relationship between video game playing and its effects on memory and mood in youth. A sample of 60 participants aged 18-40 completed a survey assessing their video game playing habits, memory, and mood. Results showed that frequent video game players demonstrated improved spatial memory and problem-solving skills, but also experienced increased symptoms of anxiety and depression. Furthermore, excessive video game playing (>4 hours/day) was associated with decreased working memory capacity and lower mood scores. These findings suggest that while moderate video game playing may have cognitive benefits, excessive playing can have negative consequences for youth’s memory and mood. The study highlights the need for responsible video game playing habits and awareness about the potential risks and benefits associated with this popular form of entertainment.